Evaluation of Health Risks in the Blood Serum of People Working in the Welding Industry as a Result of Exposure to Heavy Metals in Diyala Governorate / Iraq: Evaluasi Risiko Kesehatan dalam Serum Darah Orang yang Bekerja di Industri Pengelasan sebagai Akibat dari Paparan Logam Berat di Kegubernuran Diyala / Irak - Jbara, Abdulwahab Abdulrazaq; Abed , Noora Dhyaaldain; Mohammed , Shahad Abdul Jabbar (Procedia of Engineering and Life Science, 2024)
General Background: The welding industry is associated with significant health risks due to occupational exposure to heavy metals. Specific Background: Workers in this industry are particularly vulnerable to toxic metals such as lead, cadmium, copper, iron, and zinc, which can lead to severe health issues. Knowledge Gap: There is limited data on the specific health risks and heavy metal concentrations in welders' blood serum in Diyala Governorate, Iraq. Aims: This study aims to identify the primary health risks associated with welding-related heavy metal exposure and to explore strategies to mitigate these risks. Methods: The study was conducted in several industrial areas in Diyala Governorate, where blood samples were collected from 40 welders and 40 control participants (employees and students from Diyala University). An atomic absorption spectrophotometer was used to measure heavy metal concentrations in blood serum. Results: Statistical analysis revealed significant differences in heavy metal levels between welders and the control group (P Value < 0.05), indicating higher exposure among welders. However, no significant differences were found within welder subgroups based on age, smoking status, and duration of exposure. Novelty: This study provides the first comprehensive assessment of heavy metal exposure among welders in Diyala Governorate, highlighting the urgent need for improved protective measures. Implications: The findings underscore the necessity for environmental and health authorities to implement rapid interventions to protect welders from heavy metal toxicity. Current protective measures are inadequate, as evidenced by elevated levels of lead, cadmium, nickel, and zinc in welders' blood serum. Enhanced protective practices and stricter regulations are critical to reducing these occupational health risks. Highlights: 1. Higher levels of heavy metals found in welders' blood compared to controls.2. No significant differences among welder subgroups by age, smoking, exposure duration.3. Urgent need for better protective measures and interventions in welding industry. Keywords: Welding industry, heavy metals, occupational exposure, health risks, Diyala Governorate